Cover Image, Volume 94, Issue 1. Issue 1 (6th December 2018) - Kalla, Sarita; Upadhyaya, Sushant; Singh, Kailash; Baghel, Rakesh
Abstract : The cover image is based on the Research Article Experimental and mathematical study of air gap membrane distillation for aqueous HCl azeotropic separation by Sarita Kalla et al., DOI:10.1002/jctb.5766 . Abstract : The cover image is based on the Research Article Experimental and mathematical study of air gap membrane distillation for aqueous HCl azeotropic separation by Sarita Kalla et al., DOI:10.1002/jctb.5766 .